Evaluation of long-term settlement of waste soil by hyperbolic function model - Ahmad Sulaimi Sharif-fuddin (2023)
The hyperbolic function model, under the empirical model was proposed to compute the settlement at a given time if the ultimate settlement of a landfill is known.